SPEECH STRATEGIES PERFORMED BY STEVE JOBS IN THE LAUNCHING OF IPHONE 4 - PUTRA, ANGGAYUH ADITYA BUDI UTAMA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Public Speaking, Speech, Persuasive Speech, Elements of PersuasiveSpeech, Speech Strategies, Steve Jobs, iPhone 4 Speech is one of many ways to deliver our messages.The researcher conducts a study about speech strategies that used by Steve Jobs in the Launching of iPhone 4.There are two problems to be solved in the study, namely: (1) What are the elements of persuasive speech to indicate Steve Jobs speech in launching iPhone 4 (2) What speech strategies are used by Steve Jobs in launching iPhone 4.This study uses qualitative approach since the data are in the form of words rather than number. In this study the data are the utterances from Steve Jobs as the CEO of Apple.Inc. The data are analyzed based on the theory of Public Speaking by Steven A. Beebe and Susan J. Beebe (2005).This study has found out that Steve Job appliedThe elements of persuasive speech in his Steve Jobs’ speech. Those elements are attitudes and beliefs. Some certain strategies are used in his speech when he launches iPhone 4 in 2010. Those strategies are Omission, Suspension, Rhetorical Question, and Repetition. The application of his strategies has purpose to attract the audience to buy his new product.The writer expected that the next researcher to be able to conduct a research with exploring more the elements of persuasive speech.Speechincludes in the body of communication, so we can explore about any kind of speech strategy and we should know what are the elements of speech that should to be fulfill when we want to make a memorable speech.